A GIS-based risk reduction approach for the hazardous materials routing problem in Gaziantep. Issue 6 (18th August 2017) - Özceylan, Eren; Erbaş, Mehmet; Çetinkaya, Cihan; Kabak, Mehmet
ABSTRACT: The transportation of hazardous materials assumes a fundamental importance, especially in urban areas, in order to identify possible alternative routes and to choose the route with minimum risk. Therefore, considering minimization risk rather than minimization distance to prevent a potential danger being transformed into a real event is necessary. In this article, a geographic information system (GIS)–based solution approach is developed to quantify the factors on each link in the network that contribute to a possible route. Based on the origin and destination of each shipment, the risks associated with the routes that minimize (1) the transport distance, (2) the population exposure, (3) the probability of an incident, and (4) the emergency response are evaluated. Proposed risk models are applied to fuel-oil transportation problem between resource point and 78 gasoline stations through the road network of Gaziantep city center. Results show that the proposed framework can contribute to the thought processes of policy-makers and carriers when they evaluate possible routes in order to minimize damage for transporting fuel oil.